Marginal Discrepancy of Single Implant-Supported Metal Copings Fabricated by Various CAD/CAM and Conventional Techniques Using Different Materials - Ghodsi, Safoura (Eur J Dent, 2019)
Objective  Framework patterns can be formed using various materials such as wax, acrylic resin, or composite. Frameworks can be fabricated using either conventional or computerized techniques, using additive or subtractive method. This study aimed to compare the marginal adaptation of metal copings fabricated by two computerized technologies (milling and rapid prototyping) and additive conventional methods using different materials. Materials and Methods  Seventy-two fixture analogs were mounted vertically in acrylic resin. One-piece abutments with 5.5 mm in length and 6 degrees of convergence were secured into the analogs. The experimental frameworks were fabricated using either subtractive CAD/CAM milling (by wax, soft or hard metal), additive rapid prototyping (by wax), or conventional pattern fabrication (by wax [control] or acrylic resin). Wax and acrylic resin patterns were casted in Ni-Cr alloy. Marginal discrepancy was measured in 12 points by video measuring machine. Statistical Analysis  One-way ANOVA and posthoc tests were used to detect any significant difference among the groups at α= 0.05. Results  There was a statistically significant difference among the marginal discrepancy of six groups ( p = 0.018). The Tukey test indicated a significant difference between CAD/milling of soft metal and conventional wax pattern groups ( p = 0.011); a significant difference was also reported between CAD/milling of wax patterns and control group ( p = 0.046). Conclusions  Frameworks fabricated by conventional wax-up showed the largest marginal gaps, while the marginal gap created by frameworks made of soft metal CAD/milling were the smallest. In addition, frameworks fabricated by rapid prototyping showed clinically acceptable adaptations.